Standardization in the Pharmaceutical Manufacturing of Crude Drugs (Kampillaka): Investigation on the Standardization and Production Process of Crude Drugs in Pharmaceutical Manufacturing (Journal of Advances and Scholarly Researches in Allied Education, 2019)
It is the goal of this research to investigate the production process, quality control, and criteriaof standardisation of Kampillaka in Pharmaceutical Companies. Geological Survey of India, ParshvaChemicals, Mumbai (Maharashtra), Institute of Chemical Technology, Mumbai (Maharashtra), and VJTIChemistry Lab and Department, Mumbai (Maharashtra), all in Mumbai (Maharashtra), all participated inthe current investigation. Most pharmacological methods are based on A.F.I., I. II in this research. Asyou can see, the samples came from a variety of sources. Sodhana and other pharmaceutical processeswere used to process these samples. Sodhana of crude pharmaceuticals and Marana of sodhita(purified) samples make up the bulk of the pharmaceutical procedure for the selected-crude drugKampillaka.